Adaptation of the Self-Compassion Scale for Youth (SCS-Y) in Indonesian Schools: Analysis with the Rasch Model - Dian Munawarah; Nandang Rusmana; Setiawati Setiawati; Sudaryat Nurdin Akhmad; Rahmat Siala; Akhmad Harum; Dian Munawarah; Nandang Rusmana; Setiawati; Sudaryat Nurdin Akhmad; Rahmat Siala; Akhmad Harum (Universitas Negeri Malang, 2027)
Self-compassion is one of the variables that is crucial for teenagers in responding to failure and psychological stress in a way that is adaptive. The instrument's appropriate measurement with context language and Indonesian teenagers' culture is still limited. Research: This aim tests the psychometric properties of the Self-Compassion Scale for Youth (SCS-Y) version Indonesian through the approach of Rasch modeling, including item fit, unidimensionality, and item and person reliability. Research involving 360 selected junior high school and senior high school students from the West Java and Sulawesi regions through purposive sampling. The research process consists of two phases, namely adaptation across cultures and testing psychometrics using the Rating Scale Model with the help of the software Winsteps. Research results show that structure category scale response functioning optimally without disordered threshold, all 17 items instrument declared fit with the Rasch model without There is necessary items dropped, instrument show adequate unidimensionality ( raw variance explained by measures = 34.2%; unexplained variance in 1st contrast = 11.3%), as well as excellent item reliability (0.99) and adequate person reliability (0.76–0.80) with good internal consistency (Cronbach's Alpha = 0.78). Findings: This proves that the SCS-Y version in Indonesian is a valid and reliable instrument for measuring self-compassion of Indonesian adolescents, so that it can be used as a tool for assessment in service guidance and counseling in schools, especially for needs screening of psychologically needy students and designing intervention programs based on empirical data.